2003
DOI: 10.1038/nature02145
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 is a functional receptor for the SARS coronavirus

Abstract: Spike (S) proteins of coronaviruses, including the coronavirus that causes severe acute respiratory syndrome (SARS), associate with cellular receptors to mediate infection of their target cells. Here we identify a metallopeptidase, angiotensin-converting enzyme 2 (ACE2), isolated from SARS coronavirus (SARS-CoV)-permissive Vero E6 cells, that efficiently binds the S1 domain of the SARS-CoV S protein. We found that a soluble form of ACE2, but not of the related enzyme ACE1, blocked association of the S1 domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

72
5,519
1
109

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 5,718 publications
(5,701 citation statements)
references
References 31 publications
72
5,519
1
109
Order By: Relevance
“…We produced and purified a recombinant glycoprotein (similar to that described in Ref. 10) for biochemical studies because the soluble S1 antigen could not be isolated from a virus preparation. This form of recombinant protein was used for the original description of ACE2 as the virus receptor (10) and in a number of subsequent studies examining binding activity, folding, and even the role of the disulfides of S1 (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…We produced and purified a recombinant glycoprotein (similar to that described in Ref. 10) for biochemical studies because the soluble S1 antigen could not be isolated from a virus preparation. This form of recombinant protein was used for the original description of ACE2 as the virus receptor (10) and in a number of subsequent studies examining binding activity, folding, and even the role of the disulfides of S1 (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…This protein contains two functional domains, S1 and S2, which are located in the N-and Cterminal regions, respectively. It has been previously demonstrated that the angiotensin-converting enzyme 2 on the cell surface functions as a receptor for the SARS-CoV S protein (27,28). A 193-aa small fragment within the S1 domain (S318 -510) was identified as a minimal receptor domain and contained multiple conformationdependent epitopes that induce highly potent neutralizing Abs (29,30).…”
mentioning
confidence: 99%
“…The SARS-CoV S is quite divergent from those of other CoVs, exhibiting only 20-27% overall amino acid identity (5). Recent studies indicated that the SARS-CoV S is expressed as a noncleaved glycoprotein with an apparent mass of 180-200 kDa that interacts with a functional receptor identified as angiotensin-converting enzyme 2 (12,13).…”
mentioning
confidence: 99%